2000
DOI: 10.1038/sj.bmt.1702718
|View full text |Cite
|
Sign up to set email alerts
|

Changes in height, weight and plasma leptin after bone marrow transplantation

Abstract: Summary:Short stature can be a severe side-effect of bone marrow transplantation (BMT). Because of the effect of weight changes on growth rate and on plasma insulin-like growth factor (IGF I), we analyzed changes in height and body mass index (BMI) in 53 patients given BMT. Group 1 (n = 22) was given 12 Gy total body irradiation (TBI) as six fractions, group 2 (n = 14) 10 Gy TBI (one dose), group 3 (n = 8) 6 Gy total lymphoid irradiation (one dose), and group 4 (n = 9) chemotherapy alone. At the first evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 17 publications
(16 reference statements)
1
24
0
1
Order By: Relevance
“…21 Taskinen and Saarinen-Pihkala 22 showed that the nutritional status before TBI, evaluated by muscle index, mid-arm circumference and serum transferin concentration, was positively correlated with the growth rate during the first year after TBI. We compared the increases in centimeters to increases in kilograms during pubertal growth and found a positive correlation.…”
Section: Discussionmentioning
confidence: 99%
“…21 Taskinen and Saarinen-Pihkala 22 showed that the nutritional status before TBI, evaluated by muscle index, mid-arm circumference and serum transferin concentration, was positively correlated with the growth rate during the first year after TBI. We compared the increases in centimeters to increases in kilograms during pubertal growth and found a positive correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothalamic-pituitary function was assessed in those given TBI, and plasma thyroid stimulating hormone in those given TBI or TLI. 6 Associated growth hormone deficiency was found in 29 patients (20 boys), among them, 28 had been treated with growth hormone. Associated thyroid deficiency was found in 31 patients (21 boys), who had been treated with thyroxin.…”
Section: Methodsmentioning
confidence: 99%
“…The chemotherapy protocol was as previously reported. 6 Chemotherapy was given before BMT in cases 1-22, 33 …”
Section: Patientsmentioning
confidence: 99%
“…Nyson et al 32 found that cranial irradiation leads to muscle loss and body fat in children. Couto-Silva et al 33 found that children with TBI had lower BMIs at 2 and 5 years post-HSCT than patients who were not treated with TBI. TBI might have contributed to low LBMI reported in this study, since 94% of our patients received pre-HSCT TBI.…”
Section: Effects Of Treatmentmentioning
confidence: 99%